The Role of Digital Economy and International Trade on Ecnonomic Growth in Indonesia - M Zaenal Abid (Department of Islamic Economics, Faculty of Islamic Economics and Business, Universitas Islam Negeri Sunan Kalijaga, 2023)
In recent years, economic growth has shown fluctuating numbers, one of the consequences of which is Covid-19. The digital economy utilizes fintech technology such as p2p lending has a strategic role in economic growth activities moderated by export, import, and population variables. The data in this study uses Indonesian panel data from 2020 to 2022. The data analysis technique uses the Panel Data Regression method. Based on the results of the partial test of p2p lending has a negative and significant effect, exports have a positive but not significant effect, imports have a negative and insignificant effect and population has a positive and significant effect on economic growth. The results of the simultaneous test of all variables have a significant effect on economic growth.